A Surgeon's Path What to Expect After a General Surgery Residency (Springer International Publishing, 2018)
This text provides a comprehensive review of what comes after the completion of a general surgery residency, and will serve as a valuable resource for those surgeons, residents, and medical students interested in a career in general surgery. This book reviews several areas of fellowships and how to navigate through the application process, provide a guide for finding a job, negotiating through your first position, and also discusses other difficult topics such as how to deal with malpractice lawsuits. All chapters are written by experts who have gone through the various processes.